2019
DOI: 10.3389/fmicb.2019.00874
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcin B Is Inactivated by Intrinsic Proteinase PrtP Digestion in Lactococcus lactis subsp. lactis BGMN1-501

Abstract: In our previous study we demonstrated that proteinase PrtP is able to impair bacteriocin LcnB activity, despite being produced by the same organism and encoded by the same plasmid. However, precise mechanism of this action, i.e., the exact cleavage site within LcnB bacteriocin, as well as its effect on antimicrobial activity of the resulting peptide remained vague. Here we further explored the interplay between these two proteins and defined, using mass spectrometry, that this unusual hydrolysis indeed occurs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[ 30 ] reported that Lactobacillus johnsonii can enhance the integrity of the gut barrier in mice via interactions between GAPDH and tight junction proteins. PrtP is a cell envelope protease that is generally highly expressed in Lactobacillus and can inhibit the activities of bacteriocins, thereby exhibiting strong anti-inflammatory activities [ 31 - 33 ]. Elongation factor Tu is an immunoreactive protein highly expressed in most bacteria that mediates the adhesion of Lactobacillus plantarum HC-2 and might participate in gut homeostasis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] reported that Lactobacillus johnsonii can enhance the integrity of the gut barrier in mice via interactions between GAPDH and tight junction proteins. PrtP is a cell envelope protease that is generally highly expressed in Lactobacillus and can inhibit the activities of bacteriocins, thereby exhibiting strong anti-inflammatory activities [ 31 - 33 ]. Elongation factor Tu is an immunoreactive protein highly expressed in most bacteria that mediates the adhesion of Lactobacillus plantarum HC-2 and might participate in gut homeostasis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%